An Integrated Structural and Magnetic Fabric Study to Constrain the Progressive Extensional Tectonics of the Rio do Peixe Basin, Brazil. Issue 10 (17th October 2022) - Nicchio, M. A.; Balsamo, F.; Cifelli, F.; Nogueira, F. C. C.; Aldega, L.; Bezerra, F. H. R.; Vasconcelos, D. L.; Souza, J. A. B.
Abstract: We constrained the tectonic evolution of the intracratonic Cretaceous Rio do Peixe Basin (RPB) in NE Brazil, combining structural and Anisotropy of Magnetic Susceptibility (AMS) data. We analyzed the structural features of four sites along two major faults bordering the basin, the NE‐striking Portalegre Fault and the E‐W‐striking Malta Fault. AMS data from 42 sites in the syn‐rift sandstone suggest two stretching directions driving the opening of the RPB. The early syn‐rift phase I resulted from N‐S to NNE‐SSW stretching direction with vertical σ1, producing normal fault displacement along the E‐W‐striking Malta Fault and right‐lateral transtension along the NE‐striking Portalegre Fault, Sítio Saguí and Lagoa do Forno faults. The syn‐rift phase II resulted from NW‐SE stretching direction with vertical σ1, causing normal displacement on NE‐striking major faults and left‐lateral transtension on E‐W‐striking major faults. Additionally, the NW‐SE extension was responsible for forming NE‐striking extensional faults and deformation bands in sedimentary units. The RPB developed due to the intraplate deformation of the Borborema Province during the early stage of the Pangea Breakup and recorded two stretching directions that gradually shifted from NNE‐SSW to NW‐SE as a consequence of the South America clockwise rotation. The extensional stress orthogonal to the main E‐W‐striking and NE‐striking Precambrian shear zones facilitated the opening and evolution of the RPB. Key Points: Anisotropy of Magnetic Susceptibility (AMS) and structural analysis constrained the tectonic evolution of the Rio do Peixe Basin The N‐S to NNE‐SSW extension is associated with the syn‐rift phase I. The NW‐SE extension occurred during syn‐rift phase II The stretching direction gradually shifted from NNE‐SSW to NW‐SE due to clockwise rotation of the main stress fields associated to Pangea Breakup